Membandingkan Greenstone Digital Library (GSDL) dan Ganescha Digital Library (GDL) - Zuhdy Tafqihan (Pustakaloka, 2010)
Using digital library software should consider several things. For information providers (read; library), ease of installation and maintenance of a software deserves attenttion because the human resources (HR) that can controls the information and communication technology is still very limited. For information seekers (read: library user), a software capability in providing the most appropriate source of information about what he wants is a primary consideration. Greenstone Digital Library (GSDL) and Ganescha Digital Library (GDL) are two devices that decent alternatives to link these two desires.